2020
DOI: 10.1111/dme.14266
|View full text |Cite
|
Sign up to set email alerts
|

Trends in pregnancy outcomes for women with gestational diabetes mellitus in Sweden 1998–2012: a nationwide cohort study

Abstract: Aim To assess whether incidence of maternal and neonatal outcomes for women with or without gestational diabetes mellitus (GDM) have changed over time. Methods Population-based cohort study in Sweden including all singleton pregnancies over the period 1998-2012. GDM was diagnosed following Diabetic Pregnancy Study Group 1991 criteria. Poisson regression or negative binomial regression was used to model yearly relative change in numbers of cases and incidence of the outcomes with 95% confidence intervals (CI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…In addition, maternal age has been identi ed as another adverse factor, since its increase over the past years in high-income countries has been associated to a higher risk of GDM. In this regard, mean age in our cohort was almost 35 years, which is slightly higher than what has been reported in some previous studies [21][22][23], and this may have in uenced the total prevalence of obesity and GDM in our cohort.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, maternal age has been identi ed as another adverse factor, since its increase over the past years in high-income countries has been associated to a higher risk of GDM. In this regard, mean age in our cohort was almost 35 years, which is slightly higher than what has been reported in some previous studies [21][22][23], and this may have in uenced the total prevalence of obesity and GDM in our cohort.…”
Section: Discussioncontrasting
confidence: 62%
“…The findings of the study showed that maternal hyperglycaemia independently increased the risk of preterm delivery, caesarean delivery, infants born large for gestational age, admission to a neonatal intensive care unit, neonatal hypoglycaemia, and hyperbilirubinaemia 6. The obstetric risks associated with diabetes, such as pregnancy induced hypertension, macrosomia, congenital malformations, and neonatal hypoglycaemia, have been reported in several large scale studies 789101112. The HAPO study did not adjust for some confounders, however, such as maternal body mass index, and did not report on stillbirths and neonatal respiratory distress syndrome, raising uncertainty about these outcomes.…”
Section: Introductionmentioning
confidence: 84%
“… 6 The obstetric risks associated with diabetes, such as pregnancy induced hypertension, macrosomia, congenital malformations, and neonatal hypoglycaemia, have been reported in several large scale studies. 7 8 9 10 11 12 The HAPO study did not adjust for some confounders, however, such as maternal body mass index, and did not report on stillbirths and neonatal respiratory distress syndrome, raising uncertainty about these outcomes. Other important pregnancy outcomes, such as preterm delivery, neonatal death, and low Apgar score in gestational diabetes mellitus, were poorly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking was defined as smoking or exposure to secondhand smoke during pregnancy (yes, no), and history of allergy as any allergic diseases or symptoms ever diagnosed in pregnant women before and during pregnancy (yes, no). Gestational diabetes mellitus (GDM) was diagnosed according to the International Association of the Diabetes and Pregnancy Study Group (IADPSG; yes, no) 20 . Seasons of FFQ were defined as spring (March–May), summer (June–August), fall (September–November), and winter (December–February).…”
Section: Methodsmentioning
confidence: 99%